Analisis Perbedaan PSAK 1 Revisi 2013 dengan IAS 1 Tentang Penyajian Laporan Keuangan dan PSAK 3 Revisi 2016 dengan IAS 34 Tentang Laporan Keuangan Interim - M Fauzan Aziz; Elina Syafitri; M Luthfy Abdul K; Fajar Panji G; M Shafta Putra (CV. Ulil Albab Corp, 2022)
An interim financial report is a financial report that includes complete financial statements as described in PSAK No. 1 but in an interim period, or a time span of less than one year. This study aims to explain the comparison of policies that regulate PSAK No. 3 in the preparation of interim financial statements. The method used in this paper is a literature study, where the author collects several relevant national and international journals as the main source for this writing. The results show that the difference between PSAK and IAS is not significantly different. This is due to various factors and conditions in Indonesia. This study reveals that (1) under the supervision of PSAK, IAS does not regulate capital market regulations. (2) PSAK 1 still approves the use of the word